Exploring attention restorative theory and its use in fatigue management. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Kirshbaum, Marilyn N Y; Purcell, Brigid; Graham, Joanne; Phillips, Stephen; Malone, Jackie; Kaye, Vicky
Abstract : Background: Fatigue is a common and distressing symptom of long term illness, palliative care conditions and cancer, and a concern for families, carers and healthcare practitioners. Attention Restorative Theory (ART) was developed by Kaplan (2001) following his interest in restoring mental attention within the 'person-environment interaction'. Within this framework, restorative activities have aspects of 'being away' (ie, distinct from routine), 'fascination', 'extent' (ie, scope) and 'compatibility'. Aims: To explore the routines and activities of fatigue suffers to determine which activities are enjoyed and could be seen to reduce mental fatigue. To analyse identified activities within an ART framework to determine core attributes of potentially beneficial interventions. Method: A qualitative ethnographic approach was used to obtain knowledge about a discrete population of people who suffer from fatigue as a result of a long term illness or palliative care condition. A purposive sample of 25 participants was selected according to diagnosis, age and disability from identified contacts within the local hospice, a podiatry clinic and service user representative groups. Those who had severe mental illness, a chronic fatigue syndrome or were under 18 years of age were excluded.Semistructured interviews lasting no more 45 min were conducted using an interview guide where the emphasis was on describing activities that are enjoyed, rather than dwelling on the limitations of fatigue. Results: Early analysis has identified activities such as: involvement in creative arts, baking, reading (all sorts), watching motor bike racing, singing or having a facial, as would be expected based upon individual personalities and characteristics. Upon further examination, two clear attributes emerged; activities had to have an aspect of assured safety or social interaction. Mental restoration attributes were also prominent. Conclusions: The ART approach has interesting prospects and scope within fatigue management. Further research is required to explore and test potential implications.